2006
DOI: 10.1111/j.1365-2036.2006.02940.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of the efficacy of renzapride on gastrointestinal motility and symptoms in patients with constipation‐predominant irritable bowel syndrome

Abstract: SUMMARY AimTo investigate the efficacy and safety of renzapride, a potent 5-hydroxytryptamine type-4 receptor full agonist and 5-hydroxytryptamine type-3 receptor antagonist in patients with constipation-predominant irritable bowel syndrome. MethodsIn this dose-escalating pilot study, 17 patients with constipation-predominant irritable bowel syndrome received placebo, renzapride 2 mg o.d. and renzapride 2 mg b.d. sequentially for 28 days. Response was determined by radio-opaque marker measurement of overall ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 36 publications
1
29
0
1
Order By: Relevance
“…Acceleration of colon transit positively correlated with improvements in ease of passage and stool form, but not with stool frequency. In another study, Tack et al 106 found that renzapride at a dose of 2 mg twice daily produced a statistically significant reduction in overall colonic transit measured with radio-opaque markers compared with placebo. IBS symptoms showed some improvement with renzapride compared with placebo but did not reach statistical significance although sample sizes were small.…”
Section: The Current Approach To Drug Developmentmentioning
confidence: 97%
“…Acceleration of colon transit positively correlated with improvements in ease of passage and stool form, but not with stool frequency. In another study, Tack et al 106 found that renzapride at a dose of 2 mg twice daily produced a statistically significant reduction in overall colonic transit measured with radio-opaque markers compared with placebo. IBS symptoms showed some improvement with renzapride compared with placebo but did not reach statistical significance although sample sizes were small.…”
Section: The Current Approach To Drug Developmentmentioning
confidence: 97%
“…So, taking the binding and functional results together, they indicate that it is unlikely that renzapride would show any significant selectivity in vivo. This is a relevant consideration because the efficacy of renzapride has been established in treating patients with cIBS [16] and it is currently in phase III clinical trial for prokinetic effect in the upper gut [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Es handelt sich dabei sowohl um einen 5-HT 4 -Rezeptor-Agonisten als auch um einen 5-HT 3 -Rezeptor-Antagonisten, der stimulierende Effekte auf die gastrointestinale Motilität und den Transit aufweist [19,20]. Dabei ist das Medikament für die beiden Indikationen funktionelle Obstipation wie auch Reizdarmsyndrom mit vorwiegender Obstipation untersucht worden.…”
Section: Renzapridunclassified